The Lived Experiences of Nursing Students in Using ChatGPT to Learn English for Specific Purposes: A Phenomenological Study - Amanda Nurul Hidayah; Ikhsanudin Ikhsanudin; Endang Susilawati; Urai Salam; Yohanes Gatot Sutapa Yuliana (Interling : International Journal of English Language Teaching, Literature and Linguistics, 2026)
Although ChatGPT has been widely utilized to aid English language learning, previous studies have focused mostly on learning outcomes rather than students’ lived experiences in ESP contexts. Thus, this study examines nursing students’ experiences in using ChatGPT to learn English for Specific Purposes (ESP). The study used a qualitative phenomenological design to investigate how students perceive and interpret ChatGPT in academic and professional settings. Purposive sampling was used to choose five nursing students because phenomenological research places more emphasis on gathering detailed, rich narratives of participants’ lived experiences than on getting a large sample size. Data were gathered via semi-structured interviews and documentation, which included prompts and screenshots of participants’ activities with ChatGPT. The data were analyzed according to Moustakas’S phenomenological methods. The results show that ChatGPT is an effective tool for learning English, accessing nursing-related literature, generating ideas, and assisting with academic works. It boosts students’ confidence and motivation, while decreasing anxiety. Students participate critically and reflectively by questioning ChatGPT’s interpretations, analyzing evidence, exploring alternate hypotheses, and comparing knowledge with classmates and lecturers. Nursing students’ use of ChatGPT is influenced by their disciplinary background, making it more purposeful and applicable to their professional demands. However, the findings also reveal limitations, including inconsistent and overly general responses. The findings emphasize the necessity of teaching students how to use ChatGPT critically and ethically in ESP learning.